Kewenangan Absolut Pengadilan Agama Dalam Penyelesaian Sengketa Ekonomi Syariah Pasca Putusan Mahkamah Konstitusi Nomor 93/PUU-X/2012 - Ahmad Baihaki; M. Rizhan Budi Prasetya (KRTHA BHAYANGKARA, 2021)
After the Law Number 3 of 2006 concerning Amendments to Law Number 7 of 1989 concerning Religious Courts was ratified, the authority of the Religious Courts was expanded so as to resolve sharia economic disputes. However, ironically, Law Number 21 of 2008 concerning Islamic Banking regulates the possibility of a choice of forum (choice of forum) which Competent Court is desired by the parties to the contract, both the Religious Courts and the District Courts. As a result, in judicial practice, there are several cases of sharia economic disputes that are resolved through the general court mechanism. This research is very important to find out the authority of the Religious Courts before and after the issuance of the Constitutional Court's decision Number 93/PUU-X/2012 and its implications for the authority of the Religious Courts towards sharia banking and other sharia economic institutions. The method used in this research is a normative juridical (juridical-dogmatic) research method with a statutory and case approach. Based on the results of the study, it was found that the authority for resolving sharia economic disputes at the Religious Courts before the Constitutional Court Decision occurred dualism in the authority to adjudicate between the Religious Courts and the District Courts due to a conflict between the laws and regulations, namely Article 55 paragraph (2) of Law Number 21 of 2008 and Article 49 of Law Number 3 of 2006 and of the 1945 Constitution Article 28D paragraph (1) concerning the right of everyone to obtain rule of law. However, after the issuance of the Constitutional Court's decision Number 93/PUU-X/2012, the Religious Courts were declared as the only judicial institution authorized to resolve sharia economic disputes. This Adjudication normatively does not only have implications for Islamic banking as one of the Islamic economic institutions, but also other institutions that run their business based on sharia principles.